Cattle Grubs - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS)
Cattle grubs (Figure 1) are the immature stages of warble flies or heel flies (Figure 2). Two species of cattle grubs occur in the United States -- the common cattle grub, Hypoderma lineatum, and the northern cattle grub, Hypoderma bovis. The common cattle grub is found in Florida; however the northern cattle grub is usually found in cattle shipped to Florida from other states. Recent observations have indicated that the northern cattle grub may be becoming established in Florida. This document is ENY-270 (IG126), one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date: May 1995. Revised: March 2006.